Acute pancreatitis due to papillary stenosis in a 19-year-old patient - Piñeyro, Juan P; Farcic, Antonio; Geninazzi, Héctor; Parodi, Hernán; Delgado, Bolívar (Cirugía del Uruguay, 1977)
A 19-year-old patient suffered acute pancreatitis secondary to primitive odditis. During the first operation, cholecystostomy and pancreatic drainage were perfomed. Two months later the patient was reoperated and papillo§phyncterotomy, cholecystectomy and transcystic drainage were performed. Final evolution was good.